Antimicrobial Usage, Susceptibility Profiles, and Resistance Genes in Campylobacter Isolated from Cattle, Chicken, and Water Samples in Kajiado County, Kenya - Wanja, Daniel W.; Mbuthia, Paul G.; Bebora, Lilly C.; Aboge, Gabriel O.; Ogoti, Brian (International Journal of Microbiology, 2023)
Campylobacter organisms are the major cause of bacterial gastroenteritis and diarrhoeal illness in man and livestock. Campylobacter is growingly becoming resistant to critically crucial antibiotics; thereby presenting public health challenge. This study aimed at establishing antimicrobial use, susceptibility profiles, and resistance genes in Campylobacter isolates recovered from chicken, cattle, and cattle-trough water samples. The study was conducted between October 2020 and May 2022 and involved the revival of cryopreserved Campylobacter isolates confirmed by PCR from a previous prevalence study in Kajiado County, Kenya. Data on antimicrobial use and animal health-seeking behaviour among livestock owners (from the same farms where sampling was done for the prevalence study) were collected through interview using a pretested semistructured questionnaire. One hundred and three isolates (29 C. coli (16 cattle isolates, 9 chicken isolates, and 4 water isolates) and 74 C. jejuni (38 cattle isolates, 30 chicken isolates, and 6 water isolates)) were assayed for phenotypic antibiotic susceptibility profile using the Kirby–Bauer disk diffusion method for ampicillin (AX), tetracycline (TE), gentamicin (GEN), erythromycin (E), ciprofloxacin (CIP), and nalidixic acid (NA). Furthermore, detection of genes conferring resistance to tetracyclines (tet (O), β-lactams (blaOXA-61), aminoglycosides (aph-3-1), (fluoro)quinolones (gyrA), and multidrug efflux pump (cmeB) encoding resistance to multiple antibiotics was detected by mPCR and confirmed by DNA sequencing. The correlation between antibiotic use and resistance phenotypes was determined using the Pearson’s correlation coefficient (r) method. Tetracyclines, aminoglycosides, and β-lactam-based antibiotics were the most commonly used antimicrobials; with most farms generally reported using antimicrobials in chicken production systems than in cattle. The highest resistance amongst isolates was recorded in ampicillin (100%), followed by tetracycline (97.1%), erythromycin (75.7%), and ciprofloxacin (63.1%). Multidrug resistance (MDR) profile was observed in 99 of 103 (96.1%) isolates; with all the Campylobacter coli isolates displaying MDR. All chicken isolates (39/39, 100%) exhibited multidrug resistance. The AX-TE-E-CIP was the most common MDR pattern at 29.1%. The antibiotic resistance genes were detected as follows: tet (O), gyrA, cmeB, blaOXA-61, and aph-3-1 genes were detected at 93.2%, 61.2%, 54.4%, 36.9%, and 22.3% of all Campylobacter isolates, respectively. The highest correlations were found between tet (O) and tetracycline-resistant phenotypes for C. coli (96.4%) and C. jejuni (95.8%). A moderate level of concordance was observed between the Kirby–Bauer disk diffusion method (phenotypic assay) and PCR (genotypic assay) for tetracycline in both C. coli (kappa coefficient = 0.65) and C. jejuni (kappa coefficient = 0.55). The study discloses relatively high resistance profiles and multidrug resistance to antibiotics of critical importance in humans. The evolution of the multidrug-resistantCampylobacter isolates has been linked to the use and misuse of antimicrobials. This poses a potential hazard to public and animal health, necessitating need to reduce the use of antibiotics in livestock husbandry practice coupled with stringent biosecurity measures to mitigate antimicrobial resistance.